2007
DOI: 10.1002/bies.20546
|View full text |Cite
|
Sign up to set email alerts
|

The origins of polypeptide domains

Abstract: SummaryThree decades ago Gilbert posited that novel proteins arise by re-shuffling genomic sequences encoding polypeptide domains. Today, with numerous genomes and countless genes sequenced, it is well established that recombination of sequences encoding polypeptide domains plays a major role in protein evolution. There is, however, less evidence to suggest how the novel polypeptide domains, themselves, arise. Recent comparisons of genomes from closely related species have revealed numerous species-specific ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Novel proteins arise typically by two processes: divergence of gene duplicates and recombination events that alter DNA sequences for existing proteins (Schmidt and Davies, 2007). One recombination-mediated evolutionary event is the internal expansion of genes to create a string of repeated protein domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel proteins arise typically by two processes: divergence of gene duplicates and recombination events that alter DNA sequences for existing proteins (Schmidt and Davies, 2007). One recombination-mediated evolutionary event is the internal expansion of genes to create a string of repeated protein domains.…”
Section: Introductionmentioning
confidence: 99%
“…One recombination-mediated evolutionary event is the internal expansion of genes to create a string of repeated protein domains. Although 10 to 20% of eukaryotic proteins contain domain repeats, their genesis is not well understood (Marcotte et al, 1999;Björklund et al, 2006;Schmidt and Davies, 2007). Nevertheless, several features seem to be shared by repetitive protein domains.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, MAPK networks regulate a similar array of processes, but genomic sequence data have revealed that, in comparison to other eukaryotes, plant genomes encode enlarged gene families of MAPK kinase kinases (MAPKKKs), MAPK kinases (MAPKKs), and MAPKs (Ichimura et al, 2002;Hamel et al, 2006). Furthermore, large-scale gene expression studies indicate that many of these genes are broadly expressed throughout the plant (Schmid et al, 2005;Schmidt, 2007). These extended gene families may have evolved to allow plants, which are sessile, to sense and respond to a continuous flux of environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the creation of new genes and new gene functions (Hurley et al, 2005;Woollard, 2005;Schmidt and Davies, 2007), two important factors in the origin of genomic and organismal complexity (Gu et al, 2002;Taylor and Raes, 2004;Sterck et al, 2007). The plasticity of a genome or species in adapting to environmental changes would be severely limited without gene duplication, because no more than two variants (alleles) exist at any locus within a diploid individual.…”
Section: Wwwintechopencommentioning
confidence: 99%